Pengaruh Media Pembelajaran Scrapbook terhadap Hasil Belajar Siswa pada Mata Pelajaran Fiqih di MTs Miftahul Ulum Al-Islamy Modung Bangkalan - Badrus Shofi; Raudlatul Jannah (Jurnal Subulana, 2020)
This article discusses the Effect of Scrapbook Learning Media on Student Learning Outcomes in Fiqh Subjects at Mts Miftahul Ulum Al-Islamy Modung Bangkalan. Learning media is an inseparable part of the teaching and learning process. A teacher must have skills in using learning media effectively and creatively to students. This study aims to determine the effect of using Scrapbook learning media on student learning outcomes in fiqh subjects at MTs Miftahul Ulum Al-Islamy. This type of research uses a quantitative approach in the form of a nonequivalent control group design. The instrument used was scrapbook learning media. The data collection techniques used were observation, pretest and posttest. Based on the results of hypothesis testing, the t-count value is 6.141 and compared with the t-table of 1.761 with degrees of freedom df = 14 and a significance level of 5%. So it can be concluded that the value of tcount 6.141> t table 1.761. then declared H1 accepted. In other words, there is an effect of using Scrapbook learning media on learning outcomes in fiqh subjects for class VIII students of MTs Miftahul Ulum Al-Islamy Modung Bangkalan.